STRATEGY OF INTEGRATION OF DAYAH SALAFIYAH CURRICULUM AND FORMAL DINIYAH EDUCATION (PDF) IN IMPROVING STUDENTS' COMPETENCIES AT DAYAH BABUSSALAM AL HANAFIYYAH - Muhammad Sariyulis; Muhammad Yunus; Yusnaini (RADJA PUBLIKA, 2025)
This study aims to comprehensively describe and analyze the design and implementation strategies for integrating the Salafiyah Dayah curriculum and Formal Diniyah Education (PDF) at Dayah Babussalam Al Hanafiyah. In line with the demands of formal recognition and globalization, traditional educational institutions such as dayah are faced with the challenge of adapting without sacrificing their Islamic identity. Dayah Babussalam Al Hanafiyah has taken a strategic policy by implementing the PDF program since 2015 to integrate the epistemology of tafaqquh fiddin with national curriculum standards. This study employed a qualitative approach with a descriptive-analytical design. Data were collected through participant observation, in-depth interviews with the dayah leadership, the head of the PDF, the teaching staff, and students, as well as a curriculum documentation study. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing. The research results show that the curriculum integration design strategy was implemented through a collaborative planning and strategic alignment approach involving various stakeholders to formulate a bi-disciplinary curriculum. The integration model implemented encompasses four main pathways: interdisciplinary-substantive (linking science with theological concepts), structural-organizational (implementing a dual schedule system), technological-convergent (using digital media), and affective through the hidden curriculum (internalizing values ​​through daily worship traditions). The implementation of this strategy is supported by visionary leadership that combines Salafiyah values ​​with modern management based on the principles of shura, amanah, and itqan. Furthermore, the effectiveness of this integration has been proven to have a significant impact on improving the holistic competence of students. Based on the competency dimension, students showed improvements in aspects of motivation and self-concept through pride in religious-academic identity, mastery of dual knowledge (yellow books and science), and 21st-century skills including critical thinking, communication, and collaboration through mubahatsah forums. In terms of character, this integration strengthens discipline and social leadership based on Islamic values. This study concludes that the integration model at Dayah Babussalam Al Hanafiyah reflects the evolution from a mono-disciplinary system to a multi-lens educational framework that is adaptive to changing times while remaining firmly grounded in tradition. These findings contribute to the development of a practical model (best practice) for integrative curriculum management in Salafiyah Islamic boarding schools in Indonesia.